HBR guide to performance management
Are your employees meeting their goals? Is their work improving over time? Understanding where your employees are succeeding--and falling short--is a pivotal part of ensuring you have the right talent to meet organizational objectives. In order to work with your people and effectively monitor their progress, you need a system in place. The HBR Guide to Performance Management provides a new multi-step, cyclical process to help you keep track of your employees' work, identify where they need to improve, and ensure they're growing with the organization. You'll learn to: Set clear employee goals that align with company objectives Monitor progress and check in regularly Close performance gaps Understand when to use performance analytics Create opportunities for growth, tailored to the individual Overcome and avoid burnout on your team.